Post-fire effects on development of leaves and secondary vascular tissues in Quercus pubescens. (16th March 2020) - Gričar, Jožica; Hafner, Polona; Lavrič, Martina; Ferlan, Mitja; Ogrinc, Nives; Krajnc, Bor; Eler, Klemen; Vodnik, Dominik
Abstract: An increased frequency of fire events on the Slovenian Karst is in line with future climate change scenarios for drought-prone environments worldwide. It is therefore of the utmost importance to better understand tree–fire–climate interactions for predicting the impact of changing environment on tree functioning. To this purpose, we studied the post-fire effects on leaf development, leaf carbon isotope composition ( δ 13 C), radial growth patterns and the xylem and phloem anatomy in undamaged (H-trees) and fire-damaged trees (F-trees) of Quercus pubescens Willd. with good resprouting ability in spring 2017, the growing season after a rangeland fire in August 2016. We found that the fully developed canopy of F-trees reached only half of the leaf area index values measured in H-trees. Throughout the season, F-trees were characterized by higher water potential and stomatal conductivity and achieved higher photosynthetic rates compared to unburnt H-trees. The foliage of F-trees had more negative δ 13 C values than those of H-trees. This reflects that F-trees less frequently meet stomatal limitations due to reduced transpirational area and more favourable leaf-to-root ratio. In addition, the growth of leaves in F-trees relied more on the recent photosynthates than on reserves due to the fire disturbed starch accumulation in the previous season. Cambial production stopped 3 weeks later in F-trees, resulting in 60 and 22% wider xylem and phloem increments, respectively. A novel approach by including phloem anatomy in the analyses revealed that fire caused changes in conduit dimensions in the early phloem but not in the earlywood. However, premature formation of the tyloses in the earlywood vessels of the youngest two xylem increments in F-trees implies that xylem hydraulic integrity was also affected by heat. Analyses of secondary tissues showed that although xylem and phloem tissues are interlinked changes in their transport systems due to heat damage are not necessarily coordinated.